A tributação do contrato de integração vertical na atividade agroindustrial - Castro, André Fernando Vasconcelos de (2025)
Although extremely important to the agro-industrial production flow, very little is said about integrated rural activity, more precisely about the vertical integration contract, which unites the countryside and industry, making this figure an object alien to the universal cultural horizon. And as he presents himself as a little-known figure, the lack of scientific research focusing on him as an object of study continues. Under this unusual mixture, of a figure of paramount importance to the socioeconomic order, but who has shallow social and scientific knowledge, this work was developed, aiming to offer elements to better conceive her in the field of Law, more specifically, in the field tax. To this end, the evolution of rural activity is explored until its symbiosis with industry is achieved, inaugurating the figure of agro-industrial activity. Legal-ontological elements are collected, based on the historical view of the contract, until the appropriate contemporary General Theory is established, particularly for agrarian contracts. Securing the conceptual and historical elements, the work begins to face, in a second stage specific to Tax Law, what treatment should be offered for each of the practices developed under this production flow that involves the integrated activity, addressing consequences within the scope of the relationship tax that involves “IPTU”, “ITR”, “ICMS”, “ISS”, employer social security contribution, “FUNRURAL”, “PIS”, “COFINS”, tax immunities for export operations, “IRPF”, “IRPJ” , and, within the scope of the new tax reform (Constitutional Amendment 132/23), “IBS” and “CBS”